2022
DOI: 10.3390/jcm11154559
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Cryopreservation in Patients with Endometriosis: Current Knowledge and Number Needed to Treat

Abstract: The rise of oocytes cryopreservation (OOC) in assisted reproductive techniques allows fertility preservation (FP) in an increasing number of indications. Endometriosis, a highly prevalent disease, potentially impairing ovarian reserve, seems, therefore, an interesting indication for it. The purpose of this study is to summarize the available evidence concerning FP by OOC in women with endometriosis and to calculate the number needed to treat (NNT). In total, 272 articles related to this topic were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…According to Coccia et al, 20–50% of women who struggle with infertility also experience endometriosis [ 20 ]. While the underlying mechanism between the pathophysiology of the disease and infertility in endometriosis is not completely understood, it is suggested that ovarian reserve is impaired through chronic inflammation, increased oxidative stress, cell cycle dysregulation, and impaired angiogenesis [ 21 ]. A study conducted by Kitajima et al found that AMH levels in peritoneal fluid were lower in women with endometriosis compared to a control group of women without the disease [ 22 ].…”
Section: Artificial Reproductive Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…According to Coccia et al, 20–50% of women who struggle with infertility also experience endometriosis [ 20 ]. While the underlying mechanism between the pathophysiology of the disease and infertility in endometriosis is not completely understood, it is suggested that ovarian reserve is impaired through chronic inflammation, increased oxidative stress, cell cycle dysregulation, and impaired angiogenesis [ 21 ]. A study conducted by Kitajima et al found that AMH levels in peritoneal fluid were lower in women with endometriosis compared to a control group of women without the disease [ 22 ].…”
Section: Artificial Reproductive Technologymentioning
confidence: 99%
“…Ovarian surgery specifically lowers AMH levels and AFC, causing a decline in fertility [ 24 ]. To combat this decline in fertility, oocyte cryopreservation has been offered as preoperative fertility preservation therapy in women with endometriosis [ 21 ].…”
Section: Artificial Reproductive Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…(Carrillo Torres et al, 2023), Many women with endometriosis experience delay between the onset of symptoms and initial diagnosis, which is mainly due to lack of awareness, which in turn affects progress of the disease and the prognosis of the condition. (Ramani Devi et al, 2021), Endometriosis surgery worsens the phenomenon induced by endometriosis itself as the disease is associated with infertility through various mechanisms, such as chronic inflammation, increased oxidative stress, impaired angiogenesis and cell cycle dysregulation (Henry et al, 2022). Evidence on women's fundamental knowledge of endometriosis and its consequences among college, medical and nursing students, is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis, as well as its surgical management, can compromise the chances of pregnancy, particularly by altering the ovarian reserve. This is why an early diagnosis, which may allow oocyte vitrification to be carried out in order to preserve the patient’s chances of fertility, is essential in the management of these women [ 20 ]. In addition to the physical consequences, endometriosis induces a deleterious effect on the psychosocial and sexual wellbeing of women and imposes a substantial economic burden from a personal and societal point of view [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%